Spectrum of Clinical Manifestations in Children With WT1 Mutation: Case Series and Literature Review - Arroyo-Parejo Drayer, Patricia; Seeherunvong, Wacharee; Katsoufis, Chryso P.; DeFreitas, Marissa J.; Seeherunvong, Tossaporn; Chandar, Jayanthi; Abitbol, Carolyn L. (Frontiers in Pediatrics, 2022)
Background Mutations of the Wilms tumor suppressor-1 gene (WT1) are associated with life-threatening glomerulopathy, disorders of sexual development, Wilm's tumor, and gonadal malignancies. Our objectives were to describe the clinical presentations, age of progression, and onset of complications of WT1 mutation through a case series and literature review. Methods A retrospective study included all patients followed at the University of Miami/Holtz Children's Hospital from January 2000 to December 2020 with a diagnosis of WT1 mutation. A literature review of WT1 mutation cases was analyzed for clinical manifestations, karyotype, and long-term outcomes. Results The WT1 mutation was identified in 9 children, median age at presentation of 0.9 years (range 1 week to 7 years). A total of four had female phenotypes, and 5 had abnormalities of male external genitalia, while all had XY karyotypes. All progressed to end-stage kidney disease (ESKD) and received a kidney transplant at a median age of 5 years (1.5–15 years). During a median time of follow-up of 9 years (range 2–28 years), there were 2 allograft losses after 7 and 10 years and no evidence of post-transplant malignancy. From 333 cases identified from the literature review, the majority had female phenotype 66% (219/333), but the predominant karyotype was XY (55%, 183/333). Of the female phenotypes, 32% (69/219) had XY sex reversal. Wilm's tumor occurred in 24%, predominantly in males with gonadal anomalies. Conclusions Early recognition of WT1 mutation is essential for comprehensive surveillance of potential malignancy, avoidance of immunosuppressants for glomerulopathy, and establishing long-term multidisciplinary management.